1976
DOI: 10.1104/pp.57.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Floral Activity in Solutions of Deoxyribonucleic Acid Extracted from Tobacco Stems

Abstract: The transition of a flowering plant from vegetative to reproductive growth is preceded presumably by biochemical changes within the shoot apex that render the apex capable of forming flowers instead of leaves. Any apex which has attained a flowering capability is considered to be in a floral state. Recently, several investigators (3,8,9,14,18,19,22,23,25,26,31) utilizing segments cut from floral branches or cut from along the stem axes in the inflorescences of flowering plants have shown that these segments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Figure 10 shows that no significant amount of denatured DNA (heavy shoulder) is present. Comparative results can be seen in Figure 7, b and e. Finally, the purified rapidly renatured DNA has been tested for floral activity by the procedure already used to demonstrate floral activity in heated-cooled DNA solution (18). The results are presented in Table II.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 10 shows that no significant amount of denatured DNA (heavy shoulder) is present. Comparative results can be seen in Figure 7, b and e. Finally, the purified rapidly renatured DNA has been tested for floral activity by the procedure already used to demonstrate floral activity in heated-cooled DNA solution (18). The results are presented in Table II.…”
mentioning
confidence: 99%
“…Taking all these results together, it has been suggested that the opposite effects of IAA on both DNA synthesis and bud expression may be connected. On this basis, it has been proposed that stem segments of vegetative and flowering plants may differ in their DNA make- been reported (18). It has been shown that solutions containing DNA from stems of flowering plants effect flowering of vegetative plants, and solutions containing DNA from stems of vegetative plants are ineffective.…”
mentioning
confidence: 99%
See 2 more Smart Citations